Frequency of Dry Socket among Patients Undergoing Dental Extractions Presenting to A Teaching Hospital, Rawalpindi: Frequency of Dry Socket among Patients Undergoing Dental Extractions - Khan, Nauman Bari; Arsalan, Ayesha; Yasir, Ayesha; Azhar, Muhammad; Ali, Misbah; Nawadat, Kanza (Pakistan Journal of Health Sciences, 2024)
A dry socket, a painful post-extraction complication, occurs when the blood clot at the extraction site is dislodged or fails to form. Understanding its prevalence is crucial for improving outcomes in dental practices. Objective: To determine the frequency of dry sockets in patients undergoing dental extraction. Methods: A cross-sectional descriptive study was carried out and two customized questionnaires were filled out over three months. One questionnaire was for patients undergoing extractions and the other was filled for patients returning with dry sockets. The study included Pakistani individuals with permanent dentition while excluding non-Pakistani individuals, children with deciduous/mixed dentition, and severely immunocompromised patients. Chi-square and Fischer’s exact tests were used to compare the frequency of dry sockets between gender and age groups. p-value of less than or equal to 0.05 was considered statistically significant. Results: Out of the 188 patients, 85 (45.2%) were males and 103 (54.8%) were females. Medically compromised patients comprised 24.5% of the study population. The overall incidence of dry sockets was 9.0%, with a slightly higher occurrence in females (9.7%), though the difference was not statistically significant (p-value=0.802). Smokers demonstrated a higher incidence of dry sockets (23.1%), which was also not statistically significant (p-value=0.099). Medically compromised patients experienced dry sockets at 17.4%, compared to 6.3% in healthy patients, suggesting a trend that did not reach statistical significance (p-value=0.363). Conclusions: It was concluded that identifying high-risk groups and promoting effective prevention and management techniques can reduce the incidence of dry sockets, leading to better outcomes and overall oral health